2004
DOI: 10.1046/j.1572-0241.2003.04021.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Course of Lamivudine Monotherapy in Patients with Decompensated Cirrhosis due to HBeAg negative chronic HBV infection

Abstract: Lamivudine significantly improves liver function in HBeAg-negative decompensated cirrhosis. However, the development of the biochemical breakthrough due to YMDD mutants is associated with fatal outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
70
1
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(78 citation statements)
references
References 23 publications
5
70
1
2
Order By: Relevance
“…This was associated with a slow improvement in liver function in most patients, as measured by a decrease in the Child-Pugh score. Similar findings have been reported in several other studies (6)(7)(8). Yao et al showed that the rate of transplantation, time to transplantation, and survival were all improved in treated patients compared with a matched control cohort (6).…”
Section: S27supporting
confidence: 84%
“…This was associated with a slow improvement in liver function in most patients, as measured by a decrease in the Child-Pugh score. Similar findings have been reported in several other studies (6)(7)(8). Yao et al showed that the rate of transplantation, time to transplantation, and survival were all improved in treated patients compared with a matched control cohort (6).…”
Section: S27supporting
confidence: 84%
“…11,14,15 Lamivudine, which was the first agent used as longterm maintenance therapy in HBeAg-negative CHB since the late 1990s, is associated with high initial on-therapy remission rates, but with progressively increasing rates of viral resistance usually followed by biochemical breakthrough phenomena. [16][17][18] The recent introduction of ADV, an agent active against both wild and mutant lamivudine-resistant HBV strains, offered an effective therapeutic option for the increasing numbers of patients with resistance to lamivudine. However, data on the clinical efficacy and particularly on the incidence of major clinical events in patients under long-term antiviral therapy are rather limited.…”
mentioning
confidence: 99%
“…However, data on the clinical efficacy and particularly on the incidence of major clinical events in patients under long-term antiviral therapy are rather limited. Besides the initial partially conflicting results on the impact of emergence of YMDD HBV mutants under lamivudine, [17][18][19][20][21][22][23] cases of liver failure have only occasionally been described, mostly in patients with preexisting cirrhosis, 21 and hepatic decompensation was recently reported to develop in fewer than 1% of 998 patients with HBeAg-positive CHB treated with lamivudine for a median of 4 years. 24 The aim of this study was to determine the incidence of major events, such as death, HCC, and liver decompensation, among patients with HBeAg-negative CHB treated with long-term nucleos(t)ide analog therapy starting with lamivudine and to compare it with the same incidence in 2 historical cohorts of HBeAg-negative CHB patients, one treated with IFN␣ and the other remaining untreated.…”
mentioning
confidence: 99%
“…Furthermore, treatment with lamivudine is associated with histologic improvement not only in terms of necroinflammatory score but also in terms of fibrosis score after long-term treatment [24] . One advantage of lamivudine is that it can be used safely in patients with decompensated cirrhosis [3][4][5][6][7][8][9][10] . In contrast to IFN-α, lamivudine is well tolerated without any significant side effects even in patients with decompensated cirrhosis.…”
Section: Discussionmentioning
confidence: 99%
“…Lamivudine is effective for controlling chronic hepatitis B and currently recommended as the first line of treatment for chronic active hepatitis B [1,2] . Even for patients with decompensated liver cirrhosis, lamivudine improves liver function and extends transplantation free intervals [3][4][5][6][7][8][9][10] . Since more than 10% of patients with chronic HBV infection are estimated to develop liver cirrhosis and may eventually suffer from decompensated liver cirrhosis or hepatocellular carcinoma, the role of lamivudine in the treatment of advanced liver disease caused by chronic HBV infection is large [11][12][13][14] .…”
Section: Introductionmentioning
confidence: 99%